Electromagnetic fields and beam dynamics simulation for the superstructure of TESLA linear collider considering field asymmetry caused by HOM and power couplers - Lalayan, M.V.; Kostin, D.V.; Sobenin, N.P.; Shvedunov, V.I.; Zavadtzev, A.A.; Dohlus, M. (Вопросы атомной науки и техники, 2001)
Some features of accelerating section field computation presented by the development of power and HOM couplers for TESLA linear collider are considered. The devices mentioned produce electromagnetic field asymmetry in the beam area, thus causing transverse kick. For this kick and its influence on beam under acceleration parameters estimation the dynamics modelling calculations were done. 3D-simulation code MAFIA was used for field computation. These data were further used in beam dynamics calculations by means of TRMTrace code. Standing wave mode was simulated while considering HOM couplers, and travelling wave in case of power couplers. Transverse kicks and focussing forces are calculated for one HOM coupler design and two coaxial FM couplers.